ACADEMIC DISHONESTY AMONG STUDENTS IN INDONESIA - Herdian; Fatin Rohmah Wahidah (Junior Scientific Researcher, 2020)
This study aimed to describe the current condition of academic dishonesty in college students in Indonesia. Participants in the study were students who are currently actively undergoing lectures at universities in Indonesia (n = 408). The research method used is a quantitative descriptive approach with data collection through an academic dishonesty scale that is built based on academic dishonesty measurements developed by McCabe and Trevino (1993) and Stone et al. (2010) and has been adapted in Indonesia by Ampuni et al (2019), that consisted of 14 items (α=0.86). The results of this study describe the most academic dishonesty of students in the medium category (45.1%). The most academic dishonesty forms used by students is collaboration, while cheating is the least used method by students. Based on these results, it is hoped that educational institutions will pay more attention to how these behaviors can be prevented.